Conscious leadership elevating humanity through business - Mackey, John. (New York Portfolio, 2020)
John Mackey started a movement when he founded Whole Foods, bringing natural, organic food to the masses and not only changing the market, but breaking the mold. Now, for the first time, Conscious Leadership closely explores the vision, virtues, and mindset that have informed Mackey's own leadership journey, providing a roadmap for innovative, value-based leadership--in business and in society.
Includes bibliographical references and index.
Keywords: Social responsibility of business